Innovation to Learn to Identify Animals with The Storytelling Method Using an Illustrated Flashcard Based on Augmented Reality - Denik Ristya Rini; Agnisa Maulani Wisesa; Retno Tri Wulandari (Research Synergy Foundation, 2023)
Knowing the characteristics of animals is one of the competencies for early childhood. To learn this topic, the teacher usually uses two-dimensional animal illustrations. Along with the times, the use of learning media with technology-based is highly recommended for use in the learning process. Responding to this, this study's main aim was to design and develop 3D flashcards as learning media based on augmented reality that can be integrated with smartphones. The developed media will be used to convey learning material about animal characteristics by recognizing their anatomy through three-dimensional flashcard illustrations and the distinctive sound of each animal. The research method used the ADDIE model. The 3D flashcards were implemented for 60 children from two classes, aged between 5 – 6 years, and four teachers. The results were obtained that 92% of children could recognize animal characteristics in each 3D flashcard scanned using a smartphone. The sound in each animal helps students recognize the type of animal they are studying more. According to the teacher, utilizing this technology greatly increases children's enthusiasm for learning. The limitation of this study is the learning method that must involve parents. The novelty of this research is a learning method that involves parents using smartphones for positive purposes in the child's learning process. Some parents are against using smartphones for early childhood, but without realizing it, the demand for technology literacy must get used to it from childhood.